Free radicals, exercise, and antioxidants - McBride, J. M.; Kraemer, W. J. (The Journal of Strength and Conditioning Research, 1999)
The relationship between free radicals, antioxidants, and exercise has become a current topic of interest. Most of the free radical production within the body involves oxygen, and thus the free radicals are often referred to as reactive or reduced oxygen species. Several mechanisms for the production of free radicals in the body have been proposed. The mitochondria and ischemia-reperfusion injury have been areas of focus. Free radicals cause cellular damage by reacting with the phospholipid bilayer of cellular membranes. This reaction results in the production of measurable end products, primarily malondialdehyde. Several studies have measured malondialdehyde as a marker for free radical production with exercise and have met with varying results. The contradiction of results in previous studies may be due to differences in the assay procedures or the physiological demand of the exercise protocols used. Vitamin E, vitamin C, and beta carotene have been suggested to combat the amount of cellular membrane breakdown that accompanies increases in free radical production. Studies have examined the effectiveness of acute antioxidant supplementation on single exercise bouts. Some evidence suggests that these vitamins combat the cellular damage caused by free radical production associated with exercise in an acute situation. However, the effectiveness of long-term antioxidant supplementation in relationship to free radical production and free radical-mediated tissue damage associated with long-term vigorous exercise programs is unknown.